2021
DOI: 10.1177/10664807211000720
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adolescent Substance Abuse on Family Quality of Life, Marital Satisfaction, and Mental Health in Qatar

Abstract: This study investigated the impact of substance-addicted adolescents on family quality of life in the Arab country of Qatar. Two groups of families were compared: families with a teenager who had a substance addiction ( n = 50) and families without such a teen ( n = 53). Results showed families with a substance-addicted teenager had a lower family quality of life, that is, lower marital satisfaction, and higher couple scores on depression, anxiety, and stress. The study suggests that the relationship between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Research has also shown that social problems of wives of addicted men is related to their social perspective and states that most of the spouses experiences social repression. They try their best to hide the problem of their husband (15). They think that everyone in their surrounding knew about their husband abuse and they choose to stay away from the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also shown that social problems of wives of addicted men is related to their social perspective and states that most of the spouses experiences social repression. They try their best to hide the problem of their husband (15). They think that everyone in their surrounding knew about their husband abuse and they choose to stay away from the community.…”
Section: Discussionmentioning
confidence: 99%
“…There are also episodes of angry touching and domestic violence by either partner when spouse has been abusing substances. Psychiatric morbidity is also common among such women (14).…”
Section: Introductionmentioning
confidence: 99%
“…Another study also suggested that alcohol abuse leads to lower marital satisfaction, lower family quality of life, and increased incidence of psychiatric issues among family members and spouse such as depression, anxiety, and stress. 18…”
Section: Discussionmentioning
confidence: 99%
“…Another study also suggested that alcohol abuse leads to lower marital satisfaction, lower family quality of life, and increased incidence of psychiatric issues among family members and spouse such as depression, anxiety, and stress. 18 So, the study concluded that AUD not only affects the physical health of an individual but also other life aspects such as mental health, education, occupation, finance, family, marital life, and social life.…”
Section: Discussionmentioning
confidence: 99%
“…Ergenlerde madde aileye etkisini araştıran bir çalışmada; bağımlı ergenlerin ailerinin evliliklerinde daha az doyum aldıkları, yaşam kalitelerinin daha düşük olduğu ve ruhsal hastalıkların daha yüksek olduğu gösterilmiştir. Bu çalışmada ailede ruhsal hastalık ile ergenlerde madde kullanımı arasında iki yönlü bir ilişki olduğu vurgulanmıştır (33).…”
Section: Tablo 1 öRneklemin Sosyodemografik Ve Klinik öZellikleriunclassified